1987
DOI: 10.1002/gj.3350220614
|View full text |Cite
|
Sign up to set email alerts
|

Ductile shear zones in the northern Red Sea Hills, Sudan and their implication for crustal collision

Abstract: In the northern Red Sea Hills. of Sudan, deformation is largely concentrated into a network of shear zones. Several of these zones strike north-south. hut the important Nakasih and Sol Hamid zones are northeast-trending, and there are also minor shear zones which strike east-west. We distinguish between massive shear zones, such as that of Nakasih. and more diffuse braided shear zones. typified by the Oko zonc. The massive type owes its character to an origin a s a reactivated oceanic suture. whereas the braid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Elsamani et al (2001) suggested that gold mineralization in the Pan-African domains should be targeted near recognized sulfide concentrations, in collapse zones of extensional basins, within accretionary sutures, and along the shear zones that formed during the 650e550 Ma orogeny. The N-S Hamisana shear zone in the northern Red Sea Hills extends for more than 300 km, with an approximate width of 50 km (e.g., Bellevier et al, 1980;Stern et al, 1989). It contains internal evidence of polyphase ductile shearing followed by brittle deformation (e.g., Almond and Ahmed, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsamani et al (2001) suggested that gold mineralization in the Pan-African domains should be targeted near recognized sulfide concentrations, in collapse zones of extensional basins, within accretionary sutures, and along the shear zones that formed during the 650e550 Ma orogeny. The N-S Hamisana shear zone in the northern Red Sea Hills extends for more than 300 km, with an approximate width of 50 km (e.g., Bellevier et al, 1980;Stern et al, 1989). It contains internal evidence of polyphase ductile shearing followed by brittle deformation (e.g., Almond and Ahmed, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The N-S Hamisana shear zone in the northern Red Sea Hills extends for more than 300 km, with an approximate width of 50 km (e.g., Bellevier et al, 1980;Stern et al, 1989). It contains internal evidence of polyphase ductile shearing followed by brittle deformation (e.g., Almond and Ahmed, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Goldfarb et al (2001) and Groves et al (2003) reported that, orogenic gold as well as base-metal sulfide deposits are typically formed during late stages of the deformational metamorphic-magmatic history of the evolving orogeny, synkinematic with at least one main penetrative Elsamani et al (2001) gold mineralization in the PanAfrican domains should be targeted near recognized sulfide concentrations, in collapse zones of extensional basins and along the shear zones that formed during the 650-550 Ma orogeny. The GAH area located at the extreme northern portion of the HSZ, this shear zone contains internal evidence of polyphase ductile shearing followed by brittle deformation (Almond and Ahmed 1987). In GAH area structural controls are observed at different scales from a map-scale to a microscopic scale.…”
Section: Discussionmentioning
confidence: 99%
“…2). These cross-cutting structures form N-to NNW-trending, 30 km wide complex deformational belt (Almond and Ahmed, 1987;Abdelsalam, 1994).…”
Section: Geology Of the Nakasib Suture And The Oko Shear Zonementioning
confidence: 99%
“…2; Abdelsalam, 1994). The intersection of the Oko Shear Zone and the Nakasib Suture forms a $30 km wide belt of complex deformation (Almond and Ahmed, 1987).…”
Section: Introductionmentioning
confidence: 99%